Sorption and transport characteristics of europium on sandy soils. (April 2023) - Sheha, Reda R.; El-Shazly, Ehab A.A.; Roushdy, Ahmed F.; Salah, Bahaa A.; Kandil, Abd-Elhakim T.
Abstract: Radioactive europium can be released as a fission product during nuclear incidents and pose a threat to the human and surrounding environment because of its biological activity and long decay half-lives. For safe design issues and human health protection demands in construction of the planned nuclear power plants (NPPs) at Al-Dabaa site, it is necessary to study the sorption and transport of different radionuclides as europium within the selected area for predicting their fate at any crisis. Many soil samples were collected from different locations at the area selected along the northwestern coast of Egypt. The samples were transported to the laboratory, preserved, and characterized using X-Ray fluorescence (XRF), Fourier transform infrared spectroscopy (FT–IR), and X-Ray diffraction (XRD). Experiments were performed to study the sorption and transport kinetics of Eu(III) ions on two sandy soil samples from the collected ones. The effect of different parameters ( e.g . contact time, pH, initial europium concentration, and temperature) on the sorption behavior europium was explored in a static condition. The maximum sorption capacity was determined and found to be 3.4 and 7.0 mg g −1 for sorption of Eu(III) ions onto soil-1 and soil-2, respectively. Different models were applied to assess the sorption of europium onto the surface of the investigated soils. Data confirmed that Eu retention was attained through a chemisorption process. Further, the thermodynamic parameters were determined and their values confirmed the endothermic nature of the sorption process. The transport of europium radionuclides, with groundwater, through homogeneous porous media with uniform one-dimensional flow in the geosphere was processed and the relative migration velocity was determined in presence of both distilled and seawater media. The transport of Eu(III) radionuclides was higher in presence of seawater than that in presence of distilled water by about two order of magnitude. This obviously clarified the effect of seawater in accelerating the transport of radionuclides with groundwater in the geosphere of studied area. The role of different competing ions have various valances on the relative migration velocity was explored. Further, the time required for studied radionuclides to reach Mediterranean Sea was determined. Highlights: Sandy soil samples was collected from Al-Dabaa NPPs site and fully characterized. Europium was retained on these soils by different affinities through an chemisorption process. The loaded soils were regenerated using FeCl3 that exhibited a superior efficiency. Europium diffusion and transport were fully explored. Seawater highly accelerated the transport of Eu radionuclides in the vicinity of NPPs.